دور التسويق الداخلي في تحقيق الرضا الوظيفي للعاملين، دراسة تطبيقية على مستوى الشركة الوطنية للتأمينات (saa) بالشلف (الجزائر) - مخلوف, فاطمة; قارة, ابتسام (جامعة الوادي - University of Eloued, 2022)
This study aims to show the dimensions of inbound marketing and its importance in achieving job satisfaction, while trying to find a relationship between inbound marketing and achieving job satisfaction from the point of view of the employees of the National Insurance Company in the Gulf, where the study community is represented by the total employees of the National Insurance Company, where 40 valid electronic responses were retrieved for statistical analysis using the statistical package program.to test the hypotheses of the study and achieve its objectives. We have concluded in the Applied study that there is a statistically significant impact of internal marketing dimensions on job satisfaction in the National Insurance Company, and we have observed a statistically significant impact between each dimension of internal marketing and job satisfaction.
The role of internal marketing in achieving job satisfaction for employees .An applied study at the National Insurance Company (SAA) in Chlef (Algeria)
مقال
Keywords: التسويق الداخلي ; الرضا الوظيفي، التأمينات ; الشركة الوطنية للتأمينات